2019
DOI: 10.1002/ejp.1393
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of memantine for the prevention or treatment of chronic pain

Abstract: Background and Objective N‐methyl‐D‐aspartate (NMDA) receptors are involved in pain signalling and neuroplasticity. Memantine has been shown to have analgesic properties in pre‐clinical and small clinical studies. We conducted a systematic review and meta‐analysis to assess the efficacy of memantine to prevent or reduce chronic pain. Databases and data treatment MEDLINE, EMBASE and CENTRAL databases were searched for comparative trials using memantine, either against placebo or active medications, for chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…49 Another review and meta-analysis looking at memantine for treating or preventing pain observed considerable variation in the dose and duration of its treatment. 19 The other factors that could potentially affect the outcomes include conversion of VATS to open surgeries and the use of continuous epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Another review and meta-analysis looking at memantine for treating or preventing pain observed considerable variation in the dose and duration of its treatment. 19 The other factors that could potentially affect the outcomes include conversion of VATS to open surgeries and the use of continuous epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…17 Based on the available evidence, use of ketamine and memantine has the potential to decrease the chances of PPSP. 18,19 Steroids are potent antiinflammatory agents affecting both inflammatory and immune pathways. 20,21 Among the commonly used agents, dexamethasone is nearly five times as potent as methylprednisolone and has a biological half-life of 36-72 hrs.…”
Section: Burden Of the Problem And Etiological Considerationsmentioning
confidence: 99%
“…A double-blind, randomized-controlled trial published in 2014 found memantine to achieve a significant reduction in pain [33], with another hypothesis suggesting the combined use of pregabalin and memantine to concomitantly affect voltage-gated calcium channels and NMDA receptors, as a possible therapeutic approach [82]. A recent meta-analysis of 15 studies regarding the benefit of memantine in treating chronic pain (either neuropathic or FMS) concluded that the current evidence regarding memantine for chronic pain is limited and reported an increase in dizziness as a side effect of the medication [34].…”
Section: Nmda Antagonistsmentioning
confidence: 99%
“…Glutamate receptor antagonists have been assessed in EAE, primarily in the context of neuroprotection, prevention of demyelination, and improvement of motor deficits ( 144 148 ). Although glutamate receptor antagonists, including memantine ( 149 151 ) or modulators of the glutamatergic system such as ketamine ( 152 , 153 ) have been used for the relief of chronic pain in various diseases or injuries, their effectiveness in the alleviation of neuropathic pain during EAE/MS has not been adequately investigated.…”
Section: Role Of Activated Glia and Glia-neuron Interactions In Neuropathic Painmentioning
confidence: 99%